Design of a Proteolytically Stable Sodium-Calcium Exchanger 1 Activator Peptide for In Vivo Studies - Wanichawan, Pimthanya; Skogestad, Jonas; Lunde, Marianne; Støle, Thea Parsberg; Stensland, Maria; Nyman, Tuula A.; Sjaastad, Ivar; Sejersted, Ole M.; Aronsen, Jan Magnus; Carlson, Cathrine Rein (Frontiers in Pharmacology, 2021)
The cardiac sodium–calcium exchanger (NCX1) is important for normal Na+- and Ca2+-homeostasis and cardiomyocyte relaxation and contraction. It has been suggested that NCX1 activity is reduced by phosphorylated phospholemman (pSer68-PLM); however its direct interaction with PLM is debated. Disruption of the potentially inhibitory pSer68-PLM-NCX1 interaction might be a therapeutic strategy to increase NCX1 activity in cardiac disease. In the present study, we aimed to analyze the binding affinities and kinetics of the PLM-NCX1 and pSer68-PLM-NCX1 interactions by surface plasmon resonance (SPR) and to develop a proteolytically stable NCX1 activator peptide for future in vivo studies. The cytoplasmic parts of PLM (PLMcyt) and pSer68-PLM (pSer68-PLMcyt) were found to bind strongly to the intracellular loop of NCX1 (NCX1cyt) with similar KD values of 4.1± 1.0 nM and 4.3±1.9 nM, but the PLMcyt-NCX1cyt interaction showed higher on/off rates. To develop a proteolytically stable NCX1 activator, we took advantage of a previously designed, high-affinity PLM binding peptide (OPT) that was derived from the PLM binding region in NCX1 and that reverses the inhibitory PLM (S68D)-NCX1 interaction in HEK293. We performed N- and C-terminal truncations of OPT and identified PYKEIEQLIELANYQV as the minimum sequence required for pSer68-PLM binding. To increase peptide stability in human serum, we replaced the proline with an N-methyl-proline (NOPT) after identification of N-terminus as substitution tolerant by two-dimensional peptide array analysis. Mass spectrometry analysis revealed that the half-life of NOPT was increased 17-fold from that of OPT. NOPT pulled down endogenous PLM from rat left ventricle lysate and exhibited direct pSer68-PLM binding in an ELISA-based assay and bound to pSer68-PLMcyt with a KD of 129 nM. Excess NOPT also reduced the PLMcyt-NCX1cyt interaction in an ELISA-based competition assay, but in line with that NCX1 and PLM form oligomers, NOPT was not able to outcompete the physical interaction between endogenous full length proteins. Importantly, cell-permeable NOPT-TAT increased NCX1 activity in cardiomyocytes isolated from both SHAM-operated and aorta banded heart failure (HF) mice, indicating that NOPT disrupted the inhibitory pSer68-PLM-NCX1 interaction. In conclusion, we have developed a proteolytically stable NCX1-derived PLM binding peptide that upregulates NCX1 activity in SHAM and HF cardiomyocytes.